Improvement of Low-Waste Technology of Dairy Raw Material Processing Using New Type Membrane Equipment - Lobasenko B.; Kotlyarov R.; Sazonova E.; Vagaytseva E.; Skomorohov A. (Техника и технология пищевых производств)
Introduction. Rational use of dairy raw materials is important for the national economy. The research objective was to improve the existing technologies of milk raw material processing using new type membrane equipment with polarization layer diversion. The process was mathematically simulated according to the theory of automatic control and transfer functions. Study objects and methods. The study featured a new installation constructed on the basis of a membrane device with membrane layer diversion. The new equipment can serve as a basis for a novel low-waste and non-waste technology. Unlike traditional membrane apparatus, this one has three flows: a more concentrated polarization layer (concentrate), a core layer of retentat, and a layer of permeat. The mathematical model of the process can describe the behavior of any dynamic system of almost any structure and complexity. Results and its discussion. The simulation showed that recycling of the diverted concentrate can intensify the concentration. To increase the intensity of membrane concentration in such installations, partial recirculation of the concentrate flow can be recommended, with its subsequent transfer to the main flow. Partial recycling of the retentate flow did not prove effective, as it did no increase the concentration of the final product. However, it can be used for a more complete extraction of the target component. This aspect requires further research. Conclusions. The paper introduces a new technology that improves the concentration of milk raw materials and possesses practical importance.